2010
DOI: 10.1080/17290376.2010.9724968
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of sex work in Swaziland: barriers to and opportunities for HIV prevention among sex workers

Abstract: The HIV situation in virtually all southern African countries is a generalised epidemic. Despite the fact that almost all adult age and social groups have high HIV prevalence estimates, sex workers are disproportionally affected, with prevalence estimates higher than the general population. In a qualitative study of 61 male and female sex workers in Swaziland, we found that while poverty drove many into sex work, others reported motivations of pleasure or “sensation seeking”, and freedoms from the burden of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
(24 reference statements)
1
12
0
Order By: Relevance
“…Previous research has shown that the lives of FSWs in sub-Saharan Africa frequently include interpersonal violence, police harassment, and alcohol and drug use [14], [24][27]. Our data concur, highlighting the alcohol use, violence, and unprotected sex with sexual partners that increase FSWs' vulnerability to HIV infection.…”
Section: Discussionsupporting
confidence: 83%
“…Previous research has shown that the lives of FSWs in sub-Saharan Africa frequently include interpersonal violence, police harassment, and alcohol and drug use [14], [24][27]. Our data concur, highlighting the alcohol use, violence, and unprotected sex with sexual partners that increase FSWs' vulnerability to HIV infection.…”
Section: Discussionsupporting
confidence: 83%
“…AI practice is often more common among FSW who suffer physical [17,[19][20][21][22] or sexual violence [17,18]. Previous research on Swazi FSW points to conditions where AI is likely to be commonly practised and to frequently be condomless [23][24][25][26]. Sex work is illegal in eSwatini, and as such is hidden, marginalised and stigmatised [23,24].…”
Section: Resultsmentioning
confidence: 99%
“…However, a research reported that sex work could give them more money and pleasure, also because they did not regard life outside sex work as a viable option (Chipamaunga et al, 2010). Generally, studies found that financial need is the reason for initiating and maintaining sex work, because in some countries most of sex workers were from poor socio-economic status and broken family (Giri et al, 2012).Other factors such as lack of education, poverty, domestic violence, marital breakup, family responsibility, lack of support by family members, harassment, and abuse in society and in workplace are the main reasons for women coming to this profession as well (Charles et al, 2013).…”
Section: Become a Sex Worker:-mentioning
confidence: 99%
“…In many discussions about knowledge, attitude, and practice model, knowledge has been known as a prerequisite for the intentional performance of health-related behavior (Chipamaunga et al, 2010). Individual perception of susceptibility to HIV/AIDS and benefits of condom use are important factors in determining condom use and cognitive information through health education is an effective promotion (Ye et al, 2012).…”
Section: Knowledge Of Hiv/aids:-mentioning
confidence: 99%
See 1 more Smart Citation